Penerapan Model Pembejaran Kooperatif Tipe Students Teams Achievement Divisions (STAD) Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas V SD Negeri 016 Rambah Hilir Tahun Pelajaran 2016/2017 - Tarneka Tarneka (Indonesian Journal of Basic Education, 2018)
This study aims to improve the learning outcomes of Mathematics by applying STAD Type Co-operative learning model to students in grade V of public elementary school 016 Rambah Hilir T.P 2016/2017. The subjects of the study were grade V SD Negeri 016 Rambah Hilir with a total of 20 students consisting of 12 men and 8 women. The type of research is classroom action research. The research procedure consists of planning, implementation of action, observation and reflection. Instrument research in the form of learning tools and data collection tool sheets test dn student observation sheet. The results showed that students' absorption in cycle I was 71.5 while in cycle II was 83. For complete learning individually was on cycle I (77,5%) and cycle II (92,5%) while student activity on cycle I is (59,5%) and cycle II that is (81,5%). Thus the application of STAD Model Co-operative Learning Model to improve student learning outcomes in grade V SD Negeri 016 Rambah Hilir T.P 2016/2017